Climate Variability and Migration: Evidence from Tanzania - Mathilde Maurel; Zaneta Kubik (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
We analyze whether Tanzanian households engage in internal migration as a response to weather-related shocks. Our findings confirm that climate shocks lead to a higher probability of migration by reducing agricultural yields, which in turn induces households to send their members away in order to spatially diversify their income. This effect is, however, low, since a 1% reduction in agricultural income induced by weather shock increases the probability of migration by 3% for an average household. What is more, such mechanism is valid only for households whose income is highly dependent on agriculture, but is not significant for diversified livelihoods.
Keywords: O13; Q54; R23; 330